Evaluation of Partner Satisfaction with MBKM FISIP UNNES Students in 2025 - Kuncoro Bayu Prasetyo; Iwan Hardi Saputro; Rahmawati, Eni; Hany Nurpratiwi; Nabila Nurul Hawa; Jamhur; Noviani Achmad Putri; Restu Ayu Mumpuni (Universitas Negeri Semarang, 2025)
The Faculty of Social and Political Sciences (FISIP) of Semarang State University (UNNES) has sent students in the MBKM program to various partners, including government agencies, schools, companies, and other partner institutions. The success of the MBKM program is not only measured from an academic perspective, but also from the level of partner satisfaction with the performance of the students involved. This study aims to evaluate partner satisfaction with the performance of MBKM FISIP UNNES students in 2025. This descriptive study aims to evaluate partner satisfaction with the performance of MBKM students. This study uses mixed methods, namely using quantitative and qualitative approaches. The quantitative approach used is descriptive statistical analysis to measure the level of satisfaction from partner answers through frequency distribution. The qualitative approach uses thematic analysis techniques to identify patterns, themes, or insights from partner answers related to their experiences with MBKM students. The results of the study conclude that the implementation of MBKM FISIP UNNES in 2025 achieved a fairly good level of success, especially in efforts to prepare students for the world of work.